"Revised conflict tactics scales" as identifiers of intimate partner violence against women: integrative review - Ariane Gomes dos Santos, Caique Veloso, Larissa Alves de Araújo Lima, Claudete Ferreira de Souza Monteiro, Márcia Astrês Fernandes, Carla Danielle Araújo Feitosa (Revista de Enfermagem da UFPI, 2020)
DOI: https://doi.org/10.26694/reufpi.v6i3.6233